(untitled) (Medical Forum Monthly, 2026)
Introduction: Early initiation of breastfeeding (EIBF), placing the newborn to the breast within the first hour after birth, is one of the most effective and low-cost strategies to improve neonatal survival and maternal outcomes. Despite strong global advocacy, EIBF rates remain below the World Health Organization (WHO) target of 70%. Aim: This narrative review synthesizes recent evidence (2018–2025) on midwives’ roles in promoting and supporting EIBF, highlighting institutional, educational, and socio-cultural factors that influence breastfeeding initiation and continuation. Place and Duration of Study: Majmaah University, Al-Majmaah, 11952, Saudi Arabia from October 2025 till December 2025. Methods: A structured narrative review guided by the Joanna Briggs Institute (JBI) methodology and the PRISMAScR framework was conducted. Searches were performed in PubMed, CINAHL, Scopus, and Google Scholar.Studies addressing breastfeeding initiation, midwifery support, or postpartum education were included. Findings: eleven peer-reviewed studies met inclusion criteria. Evidence showed that midwives’ education and training significantly improve EIBF outcomes. Institutional policies such as Baby-Friendly Hospital Initiative (BFHI) accreditation, rooming-in, and skin-to-skin contact enhance breastfeeding success. Mothers valued empathetic communication, practical assistance, and continuity of care. Barriers included Cesarean delivery, inadequate staff training, and limited institutional support. Conclusion: Midwives are pivotal in achieving optimal breastfeeding outcomes through immediate postpartum support, advocacy, and culturally sensitive counselling. Strengthening professional education, enforcing BFHI standards, and expanding family-inclusive community programs are essential to meet WHO and Saudi Vision 2030 targets.